Die Beziehungen zwischen Frau und Mann in der Dramatik und Prosa von Dagny Juel-Przybyszewska - Kłańska, Maria (Folia Scandinavica Posnaniensia, 2016)
In Poland, the name Dagny is well-known because of the sad life and tragic death of the Norwegian wife of the famous and scandalising Polish-German fin de siécle writer Przybyszewski. But not many people know that she was a writer and poet herself, even if not a very prolific one. Her ouevre consists of four short plays, five poems in prose and a handful of poetry. The aim of this article is to analyse her plays and prose in respect of the relations between a man and a woman. Especially, I enquire if Juels work is only an expression of the literary conventions of her epoch, or if she gives her texts an unique (feminine) touch. I attempt to demonstrate that the latter is the case in her dramatic work and especially in her prose poetry.